AN IMMUNOHISTOCHEMICAL LOCALIZATION OF ENDOCRINAL CELLS IN THE EPITHELIUM OF THE DUODENUM MUCOSA OF TURKEY ( Meleagaris gallpava ) - Abdulrazzaq Baqer Kadhim (Basrah Journal of Veterinary Research)
in some parts of the intestinal tract, which play an important and primary role in the secretion of certain hormones that regulate important organs of the body. The aim of this study is to examine the site endocrine cells in the mucous layer of the five male Turkey. The areas where endocrine cells in the mucous layer of the five male in the Turkish examined by using immunohistochemistry technique material. Samples were taken from five birds from the Turkish males ages ranging from 1-2 years. It was used immunohistochemistry textile technology and (ChromograinnA), which is a special detector Endocrine intestinal cells, four types of hormones. Immune chemical examination in the mucous layer duodenum and the presence of hormones, glucose insulin tropic polypeptide(GIP) results showed (GIP) and cholecystokinin (CCK) glucagon-like peptide2 (GLP-2) in epithelial cells group along the internal axis of the villi, chemical immunological results for many of the sections shown note chromogranin A detector particularly for intestinal endocrine cells, the cells that cholecystokinin(CCK) , glucose insulin tropic polypeptide contain hormones (GIP) and glucagon peptide GLP-1 2)) containing this reagent indicating confirm the location of these cells, a gastric endocrine cells . The presence of these hormones in the mucous layer of the Duodenal decreases as we move away from the duodenal